AVALIAÃ‡ÃƒO DO USO DE FOSFINA NA PROTEÃ‡ÃƒO DE SEMENTES DE ALGODÃƒO CONTRA INFESTAÃ‡Ã•ES DE ð˜›ð˜³ð˜ªð˜£ð˜°ð˜ð˜ªð˜¶ð˜® ð˜¤ð˜¢ð˜´ð˜µð˜¢ð˜¯ð˜¦ð˜¶ð˜® HERBST, 1797 (COLEOPTERA-TENEBRIONIDAE) - Campos, TÃ©rcio Barbosa de; Imenes, Silvia de Lamonica; Bergmann, Eliana Cherubini; Xavier, NÃ©lio JosÃ© Dias; Santiago, Ivanildo Muniz (REVISTA DE AGRICULTURA, 2020)
AVALIAÃ‡ÃƒO DO USO DE FOSFINA NA PROTEÃ‡ÃƒO DE SEMENTES DE ALGODÃƒO CONTRA INFESTAÃ‡Ã•ES DE ð˜›ð˜³ð˜ªð˜£ð˜°ð˜ð˜ªð˜¶ð˜® ð˜¤ð˜¢ð˜´ð˜µð˜¢ð˜¯ð˜¦ð˜¶ð˜® HERBST, 1797 (COLEOPTERA-TENEBRIONIDAE)